Pengaruh Earnings Management Terhadap Firm Value Dengan Earnings Quality Sebagai Variabel Intervening - Ryan Chandra; Devie Deviesa (Business Accounting Review, 2017)
The purpose of this study was to know the direct affect of the earnings management toward firm value. This study also wanted to know the indirect affect of earnings management toward firm value with earnings quality as an intervening variable. This study used quantitative method by using secondary data such as annual report and financial report. The sample of this study is companies that are listed in Indonesian Stock Exchange.            The data – processing method is done by using validity, reliability, and statistic descriptive analysis. While the data analysis method is tested by using partial least square (PLS) with the Smart PLS 2.0 program. The result of this study revealed that earnings management significantly affected firm value, and indirectly affected through earnings quality as an intervening variable.